Investigating the Impact of Shading Effect on the Characteristics of a Large-Scale Grid-Connected PV Power Plant in Northwest China - Yunlin Sun; Siming Chen; Liying Xie; Ruijiang Hong; Hui Shen (International Journal of Photoenergy)
Northwest China is an ideal region for large-scale grid-connected PV system installation due to its abundant solar radiation and vast areas. For grid-connected PV systems in this region, one of the key issues is how to reduce the shading effect as much as possible to maximize their power generation. In this paper, a shading simulation model for PV modules is established and its reliability is verified under the standard testing condition (STC) in laboratory. Based on the investigation result of a 20 MWp grid-connected PV plant in northwest China, the typical shading phenomena are classified and analyzed individually, such as power distribution buildings shading and wire poles shading, plants and birds droppings shading, and front-row PV arrays shading. A series of experiments is also conducted on-site to evaluate and compare the impacts of different typical shading forms. Finally, some feasible solutions are proposed to avoid or reduce the shading effect of PV system during operation in such region.